Tinjauan Hukum Hindu Terhadap Perbuatan Zina: Perspektif Etika Dan Dharma - Sudarmini, Ni Wayan (Belom Bahadat, 2025)
Adultery, from the perspective of Hindu law, is seen as a serious violation of moral values, the sanctity of sacred relationships (grhastha asrama), and a social order based on dharma. This study aims to examine the views of Hindu law on adultery by reviewing Hindu legal sources such as the Veda Smrti, especially the Manawa Dharmasastra, Sarasamuccaya, Parasara Dharmasastra, Arthasastra, and Hindu ethical teachings based on morality and dharma. The research method used is empirical sociological research with a normative-theological approach through literature study. The results of the study indicate that adultery is categorized as adharma because it violates the principles of moral purity, honesty, and family order as the foundation of social life. Hindu law provides moral, social, and religious sanctions for perpetrators of adultery, which are not only aimed at punishment but also at educating and restoring balance through karma phala. In addition, Hindu ethical teachings emphasize self-control (indriya nigraha), loyalty (śraddhā), and responsibility in household relationships as ways to prevent adultery. Thus, Hindu law not only provides a normative legal aspect to the prohibition of adultery, but also offers an ethical and religious approach that emphasizes maintaining harmony in life based on dharma.